The Alien, the Citizen, and the Triumphant Capitalist - Gonzales, Gloria G. (Archīum Ateneo, 2024)
This paper examines notions of the “alien” and the “citizen” or the outsider and insider based on the Chinese Filipino experience as portrayed in Charlson Ong’s novel Banyaga: The Song of War (2006). Although the Chinese have lived in the Philippine archipelago since the twelfth century, they have always been considered banyaga (alien or foreigner) by Filipino “natives.” I argue that the marginalization of the Chinese has led them to specialization in trade and commerce, which in turn has steered them, paradoxically, towards exceptionalism. As such, I correlate Ong’s banyaga with Georg Simmel’s concept of the stranger and argue that “strangeness” positions the Chinese to become the “trium- phant capitalist” and “flexible citizen” as personified by the Chinese tycoon in Banyaga. Historically, the Chinese in the Philippines have been situated in the margins of society. The socio-political alienation of the Chinese in Philippine society is not only due to their race and their legal designation as aliens during various colonial and postcolonial regimes, but also from their historic role as trader, middleman, mercantilist, and capitalist. The sojourning practices and transnational connections of the Chinese have also contributed to the native’s perception of the Chinese as alien and foreign. As such, this paper also investigates how transnationalism complicates issue of citizenship, nation-making, and national formation, and how these very same transnational linkages of the Chinese have poised them to become the flexible citizens of the twenty-first century. As a counter- point to Banyaga, Ong’s earlier novel, The Embarrassment of Riches (2000), is also briefly examined in this paper. Embarrassment is a literary intervention that allows us to explore the multiple strands of national identity and the complex, even predatory, transnational processes that impact the nation-state due to increasing migration and global expansion of capitalism.